2019
DOI: 10.1111/pai.13100
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anxiety and internet‐based food elimination in suspected food allergy

Abstract: Background Food allergy is associated with stress, anxiety, and impairment in quality of life in both children and families. This study aimed to assess the anxiety of mothers in the case of suspected food allergy in their children and the influence of Internet usage on their levels of anxiety and food elimination. Methods Ninety‐two patients aged 0‐2 years presented at a pediatric allergy department following either a physicians' presumptive diagnosis or family's suspicion of food allergy (Group 1) and 99 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 26 publications
5
27
0
Order By: Relevance
“…Although there was no control group in this study, others have found higher anxiety in parents of food‐allergic children compared with controls 16 . Compared with mean STAI‐S scores from studies of mothers of patients enrolled from paediatric allergy clinics, the mean STAI‐S score for parents in this study (42.0) was higher than that reported in three studies in the United Kingdom (34.6, 36.2, 38.0), 7,17,18 and similar to a Turkish study (41.5) 19 . Normative STAI‐S data available from the Un ited Kingdom indicate a score of 33.3, 17 lower than all published studies of parents of food‐allergic children.…”
Section: Discussionsupporting
confidence: 60%
“…Although there was no control group in this study, others have found higher anxiety in parents of food‐allergic children compared with controls 16 . Compared with mean STAI‐S scores from studies of mothers of patients enrolled from paediatric allergy clinics, the mean STAI‐S score for parents in this study (42.0) was higher than that reported in three studies in the United Kingdom (34.6, 36.2, 38.0), 7,17,18 and similar to a Turkish study (41.5) 19 . Normative STAI‐S data available from the Un ited Kingdom indicate a score of 33.3, 17 lower than all published studies of parents of food‐allergic children.…”
Section: Discussionsupporting
confidence: 60%
“…[14][15][16] Eighty-six per cent of mothers of children with suspected FA avoid foods on their own initiative. 17 Goldberg et al 16 have recently shown that milk-allergic young adults have reduced bone mineral density and that low calcium intake, asthma and weight constitute independent risk factors. FA can also result in an impairment of quality of life and mental health of children and their families.…”
mentioning
confidence: 99%
“…The studies related to anxiety of parents of the children with suspected food allergy have been compared before and after OFC. The parents' anxiety level decreased after OFC [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Although anxiety associated with DPTs and OFCs has been reported [12][13][14], to the best of our knowledge, no studies that provide a quantitative assessment of parental anxiety and depression associated with these evaluations have yet been performed.…”
Section: Introductionmentioning
confidence: 99%